THE Pengaruh Abu Dasar Batubara dan Media Tanah Kompos terhadap Pertumbuhan Tanaman Cabe Merah (Capsicum annuum) - Nunung Elawati; Carmelia Santania Fahik; Arifah Nurul Izza; Fika Ainur Rahmawati (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: Coal burning activities at PLTU leave large amounts of waste every year, which can become a problem of environmental pollution. Bottom ash is known to contain nutrients needed by plants. This study aims to determine the effect of adding a mixture of compost as an ameliorant to bottom ash on the pH and plant growth of Capsicum annuum. Methods: The study used a completely randomized design (CRD) with 3 replications and 4 formulations, namely B0 = coal waste (200g); B1 = 100g of bottom ash: 100g of planting medium; B2 = 50g bottom ash: 150g planting medium, and B3 = 150g bottom ash: 50 g planting medium. Parameters observed included plant height, number of leaves, root length, number of roots, total biomass and pH. Results: The results showed that treatment B0 had the highest pH and B2 had the lowest pH. Treatment B2 successively showed the highest plant height, the largest total biomass, and the highest root length, and had a significant effect on leaf number, but had no significant effect on root number. Conclusions: Based on the results of the study showed that the application of bottom ash with soil compost media had an effect on the pH and the growth of C. annuum plants, especially on plant height, number of leaves, total biomass, and root length of C. annuum plants